As representações líricas da morte na poesia de H. Dobal - Reinaldo, Lilásia Chaves de Arêa Leão (2014)
This study called The lyrical depictions of death in H. Dobal´s poetry is dedicated to investigating expressive stylistic settings of death in the poetry of Hindemburgo Dobal Teixeira, whose poetry was observed as being deeply imbibed of the constructs of this issue of essence, which is very significant and crucial for humanity. From the assumption that it is possible to recognize a variety of ways and biases of settings of death in the poetry of H. Dobal, this study paper proposes the recognition and categorization of these poetic constructs, in order to contribute more specifically, to the critic density of this author from Piauí, and more generally, for studies of Brazilian poetry, especially with regard to the issue of death. The analytical course was undertaken in the light of studies of the critic and historian Antonio Candido in his writing focused on the themes of Brazilian literature as cultural production, which is dialectically gestated within society and carried out by agents in their relationships and contexts, transmuted into literary art, in this particular case, the poetry of H. Dobal. From the same social context as Antonio Candido, in questions of theoretical nature on literature and society, other prominent thinkers in the international sphere contributed who add to this understanding, such as Walter Benjamin and Theodor Adorno. To provide groundings to the studies pertaining to the subject of death, the study of several researchers have been associated, mainly from French Philippe Ariès and Edgar Morin, and Brazilian, Joao José Reis and Júlio José Chiavenato. As for the concepts and methods chosen for theme exploration with focus on the poetic lines, with respect to the instrumental analysis and views on the lyrical element, in addition to Antonio Candido himself, the analytic process was guided by scholars in this area of the literature, such as Emil Staiger, Mikel Dufrenne, T.S. Eliot, Paul Valery and Otávio Paz, among others. With the look always towards tracing the literary constructions of "Death", the study dived into in the exercise of scanning poetic figures in a careful analytical course, in order to bring to light what was observed as a cast of figurations of the Death issue, which reveal themselves as genuine contributions of this poet from Piauí to the literary panorama of Brazilian poetry, in the recognition , evaluation and dissemination of which this study pursues. Finally, from the findings gathered, we define a set of settings of categories of death, taken out from Dobal´s poetics, which are presented as a contribution to studies on the theme of death in the world of poetry.